Studies Of The Heterogeneity Of Purified Antithrombin III - Barrowcliffe, T W; Eggleton, C A; Mahmoud, M (Thrombosis and Haemostasis, 1981)
Deficiency of antithrombin III (At III), whether hereditary or acquired, is now recognised as a major predisposing factor for the development of venous thromboembolism. Purified At III concentrates are undergoing clinical trials in various conditions associated with At III deficiency; such concentrates may be given in addition to heparin and their potency is usually assessed by heparin co-factor assays. In an international collaborative study, a reference preparation of purified At III had a lower concentration by heparin co-factor than by immunological assays and this was shown to be due to the presence of non-heparin-binding antigens. In the present study we have examined purified At III from several manufacturers by heparin co-factor (amidolytic), progressive antithrombin (clotting) and immunological assays, and their heparin-binding abilities have been studied by crossed immunoelectrophoresis and heparin-agarose affinity chromatography.There was good agreement between progressive antithrombin and immunological assays, but in some concentrates the heparin co-factor assays gave lower activity. The proportions of non-heparin-binding material varied considerably, from less than 5% to as much as 50% of the total At III antigen in some concentrates. The non-binding material isolated from a heparin column had little heparin co-factor activity, but was able to neutralise thrombin and Factor Xa. Gel filtration and polyacrylamide gel electrophoresis showed no major distinction between heparin-binding and non-binding antigens, indicating the absence of At III-protease complexes.These studies show that some At III concentrates contain substantial amounts of partially denatured molecules, in which the heparin-binding ability of the At III has been impaired but its thrombin and Xa neutralising activity left relatively intact.